2016
DOI: 10.1177/0143831x16648386
|View full text |Cite
|
Sign up to set email alerts
|

Managing motivation in the contact center: The employment relationship of outsourcing and temporary agency workers

Abstract: Grounded in self-determination theory (SDT), this research builds a motivation profile typology of contingent workers in the contact center industry, compares outsourcer (OW) and temporary agency workers' (TAW) profiles, and differentiates their human resources practices (HRP) perceptions and affective commitment. The hypotheses were tested in a sample of 2078 Portuguese contingent workers, through several statistical procedures, including latent profile analysis. Six profiles were identified. As expected, OW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 75 publications
(131 reference statements)
3
31
0
Order By: Relevance
“…Labor flexibility’s growth and development also impacted the configuration of contingent work. From the existing contingent work formats, temporary staffing agencies have the most complex work arrangement (Sobral, Chambel, & Castanheira, 2016). Temporary agency workers (TAW) are in a three-way relationship and are capable of creating ‘dual allegiances’ (Bonet, Cappelli, & Hamori, 2013).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Labor flexibility’s growth and development also impacted the configuration of contingent work. From the existing contingent work formats, temporary staffing agencies have the most complex work arrangement (Sobral, Chambel, & Castanheira, 2016). Temporary agency workers (TAW) are in a three-way relationship and are capable of creating ‘dual allegiances’ (Bonet, Cappelli, & Hamori, 2013).…”
mentioning
confidence: 99%
“…Temporary agency workers (TAW) are in a three-way relationship and are capable of creating ‘dual allegiances’ (Bonet, Cappelli, & Hamori, 2013). They establish work relations with the temporary agency, with which they have a formal contract, and the client company, with whom they actually work (Sobral et al, 2016; Sobral, Lopes, Chambel, & Castanheira, 2015). Given this reality, several studies (e.g., Zimmerman et al, 2013) have indicated a need to adjust and adapt academic representations of labor relations to the present context.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The incentive problem has always been the core issue of management. Management scientists may be able to accurately predict, plan and control financial and material resources [8]. However, it is difficult to predict and control the human resources, especially the inner potential and effort.…”
Section: Introductionmentioning
confidence: 99%